How and Where the Birth Delivery Taking Place Matter towards the Success of Exclusive Breastfeeding - Adamina Dinda Roseprilla; Trias Mahmudiono; Qonita Rachmah (Universitas Airlangga, 2022)
Background: Breast milk is the best nutrition for babies. The coverage of exclusive breastfeeding in Indonesia in 2017 was still low. However, there are many factors that contribute to low rates of exclusive breastfeeding including socio-cultural factors, factors related to the health system, market, environment, and knowledge. Recent studies have shown that there was a relationship between the place and type of delivery with exclusive breastfeeding. Objectives: This study aimed to analyze the correlation between the place and type of delivery with the success of exclusive breastfeeding practice in Indonesia among mothers of infants 0-6 months.Methods: This study was a secondary data analysis using data from the results of the 2017 Indonesia Demographic and Health Survey (IDHS), conducted in 34 provinces in Indonesia with a total sample of 1810 infants aged 0-6 months. The dependent variable was the exclusive breastfeeding. Independent variables were mother's age, mother's level of education, parity, place of delivery, and type of delivery. Data collection was carried out for all variables by interviewing using a reproductive woman questionnaire. Data were analyzed using chi square test.Results: The results showed that 48.2% of mothers gave exclusive breastfeeding. The results of the bivariate analysis showed that the variables of place of delivery (p-value=0.045), type of delivery (p-value<0.001), and mother's age (p-value=0.048) were related to the practice of exclusive breastfeeding.Conclusions: The conclusion of this study was the factors that affecting exclusive breastfeeding in were place of delivery, type of delivery, and mother's age.Keywords: exclusive breastfeeding, place of delivery, type of delivery, early life nutrition